Citizens' Classics for the 21st Century. Issue 32 (2015) - Hall, Edith
Abstract : The recent general election has exposed the danger inherent in vote-based democracies – that they inevitably entail large disaffected minorities being excluded from executive power. The ancient Greek inventors of democracy vigorously debated this issue, having painful historical experience of it (recorded by Thucydides) and theoretical solutions (discussed by Aristotle). Yet our state educational system almost completely deprives our secondary-school children of the opportunity to think about democracy afforded by the dazzling thought-world of the ancient Greeks. This is despite the availability of excellent translations of all their writings – free online – into modern English.